南極氷床への大気輸送起源分布の季節変化 - 鈴木, 香寿恵; 山内, 恭; 川村, 賢二; 本山, 秀明; Suzuki, Kazue; Yamanouchi, Takashi; Kawamura, Kenji; Motoyama, Hideaki (2013)
Transport of moisture-bearing air to the Antarctic is one of the important factors that control the mass balance of the ice sheet. Here, we investigate the distribution of air-parcel transport using a backward trajectory analysis over the entire Antarctic ice sheet, based on whether the air parcel was located inside or outside of Antarctica at 5 days before arrival. At this time, we considered the air from outside Antarctica to be moisture rich. Oceanic air was found to dominate in West Antarctica throughout the year, whereas air from inland was more prominently distributed around East Antarctica, especially in summer. In East Antarctica, there was a significant seasonal variation: air from inland dominated in summer, while air of oceanic origin dominated in winter. The distribution of air parcels that came from oceanic/inland sources was similar to the accumulation map (based on satellite data), which indicates that oceanic air parcels could be a substitute for moisture transport to the Antarctic. To determine the future impacts of climate change (e.g., sea level rise), more precise predictions of the variations in the surface mass balance will be required. Our results contribute towards the improved understanding of the spatial distributions of accumulation and aerosols found in Antarctic snow and ice cores. 第4回極域科学シンポジウム 個別セッション：[OM] 気水圏 11月15日（金） 国立極地研究所 ３階ラウンジ conference object